Groundwater desalination using forward Osmosis in Egypt - Nasr, Peter (AUC Knowledge Fountain, 2016)
Rapid population growth is putting huge stress on limited fresh water sources in Egypt. Agriculture is considered the major consumer of fresh water in Egypt, consuming more than 80% of fresh water available. Creating new freshwater sources for irrigation purposes becomes inevitable to meet the increasing demand. Groundwater desalination could be the solution to this problem. If a low-cost sustainable desalination technology is realized, impact on the agricultural sector would be remarkable for water stressed country like Egypt. Forward Osmosis (FO) is an innovative membrane separation technology that can be applied to efficiently desalinate groundwater. FO desalination relies on the theory of natural osmotic pressure driven by concentration difference instead of hydraulic pressure in RO (Reverse Osmosis). Thus, desalination can be achieved using significantly low energy. FO desalination process involves the use of a concentrated draw solution (DS), generating elevated osmotic pressure, flowing on one side of a semi-permeable FO membrane, and a feed solution (FS), with a lower osmotic pressure, flowing by the other side. Fresh water leaves the FS and enters the DS by natural diffusion. The diluted DS is then separated from the fresh water and draw solutes are recovered. One application of FO process is Fertilizer Drawn Forward Osmosis (FDFO). This application offers a unique advantage as separation and recovery of draw solute is not essential since the draw solution adds value to the end product. The convenience of FDFO desalination is that produced water can be directly utilized for fertigation because fertilizers are needed anyway for the plants avoiding the need for separation and recovery of draw solutes. However, FDFO desalination has some limitations that should be considered. Novel draw solutions and capable FO membranes are the main concern of most FO researchers as both greatly affect overall process efficiency. The high nutrient content in product water is another limitation making meeting irrigation water quality standards a challenge. Applying FDFO technology in Egypt for augmenting irrigation water by desalinating abundant brackish groundwater is investigated in this work. As Egypt is a groundwater-rich country, application of FDFO desalination technology would lead to a revolutionary platform where unutilized brackish groundwater can be efficiently made use of to generate valuable nutrient-rich irrigation water. Egyptian irrigation schemes and mapping of groundwater aquifers in Egypt have been carefully investigated. Based on a carefully studied selection criteria, two proposed locations are suggested for this application in Egypt: 1) Nile Valley and Delta region and 2) Red Sea coast in Eastern Desert and Sinai region. In Nile valley and Delta region, it is suggested to apply FDFO technology coupled with localized irrigation instead of flood irrigation. The suggested technique could possibly cultivate 1 million feddan using renewable groudnwater. Proposed scheme will lead to a healthier Nile River and is expected to eventually minimize further soil salinization being a reported problem in the area which negatively affects crop yield In Red Sea coast in Eastern Desert and Sinai region, FDFO desalination is a promising technology to help alleviate the severe water scarcity problem inhibiting the area’s development. Already existing RO facilities could be easily integrated to the suggested FDFO technology. In this study it is suggested to have decentralized small-scale farms, instead of hundreds of thousands of feddan as is common in Delta and Nile valley regions. This will minimize water losses and keep the desalinated water at a competitive price. FDFO desalination success is greatly affected by the choice of a suitable draw solution. This study focused only on nitrogenous-based fertilizers being by far the most dominant class of fertilizers used in Egypt. Four nitrogenous Egyptian fertilizers have been closely evaluated with respect to their availability, economics and performance. The three factors played a major role in the fertilizer selection. Ammonium Sulpahte was selected to be the most suitable fertilizer draw solution exhibiting high osmotic pressure, being non-expensive, non hygroscopic, resistant to valorization, highly soluble in water and containing sulphur which is needed by the plant. Performance of ammonium sulphate DS was then tested experimentally. The FO membrane used was thin film composite (TFC) membrane supplied by Woongjin, Korea and fhe FS was synthetic salty water prepared using different concentrations of NaCl. A bench-scale FO setup was used to run the experiments. The performance was assessed based on water flux, reverse permeation and feed ions rejection at different DS concentration. It is concluded that there is a logarithmic correlation between flux and ammonium sulphate concentration where any additional increase in ammonium sulphate concentration inhibits water flux due to dilutive internal concentration polarization (DICP) effects. Increasing FS concentration leads to flux decline due to the drop in the differential bulk osmotic pressures between DS and FS. Specific Reverse Solute Flux (SRSF) values at flux less than 10 Lm-2h-1 is significantly higher than that for flux more than 10 Lm-2h-1. As a result, it is recommended to operate the process at a flux exceeding 10 Lm-2h-1 to avoid undesired loss of draw solute by reverse permeation. SRSF is almost constant irrespective of ammonium sulphate DS concentration. For the same DS concentration, flux and SRSF are inversely proportional. Except when operated at low ammonium sulphate concentration and high FS concentration, the TFC membrane used in this study exhibited high rejection of FS ions for almost all DS concentrations (more than 90%). To sensibly test the efficiency of the ammonium sulphate draw solution, a real brackish Egyptian groundwater sample was collected, analyzed and used as FS. Being available, three FO membrane samples were assessed in this part of the study and the best membrane was selected for further investigations. In comparison to HTI’s Cellulose Triacetate (CTA) and Woongjin TFC membranes, Porifera’s commercial membrane proved to be best membrane with respect to baseline flux, where DS was NaCl and FS was DI water. Having the smallest structural parameter (S), internal concentration polarization (ICP) is minimized yielding highest flux. Different concentrations of ammonium sulphate were used as DS using the BGW sample. Like previously, the performance was assessed based on water flux, reverse permeation and feed ions rejection. A logarithmic relation was drawn between water flux and ammonium sulphate concentration. Same relation existed between ammonium sulphate concentration and water flux due to DICP effects. However, in this study, SRSF values did not exceed 0.18 g/l for both NH4+ and SO42- ions, indicating high membrane selectivity. At flux exceeding 20 Lm-2h-1, NH4+ ion reported higher SRSF values than that of SO42− ion.. Again, SRSF came out to be almost constant irrespective of ammonium sulphate concentration. While increasing draw solution concentration lead to increasing Na+ ion rejection, it caused a significant decline in Cl- ion rejection. This phenomenon could be probably associated to an ion exchange mechanism and reversal of membrane surface charge. In conclusion, FDFO is a promising technology that could possibly alleviate the water scarcity problem in Egypt. Not only is FDFO a sustainable desalination technology, but also it has numerous advantages over conventional desalination technologies. Abundant brackish groundwater could be efficiently exploited to produce valuable nutrient-rich irrigation water, being the major fresh water consumer in Egypt. The scheme studied demonstrated that ammonium sulphate is an efficient DS for FDFO process, especially using Porifera’s commercial FO membrane, exhibiting high osmotic pressure, low reverse solute permeation and remarkable rejection of feed solute. The proposed scheme could lead to a technology platform that would supply supplementary irrigation water, reduce soil salinity, manage fertilizer application and close the irrigation – brackish water – drainage vicious loop.